2009
DOI: 10.1211/jpp.61.06.0009
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of JBP485 on concanavalin A-induced liver injury in mice

Abstract: These results indicated that immune-mediated liver damage can be prevented by JBP485, and that this is mainly associated with immunomodulatory effects on T cells and adhesion molecules, antioxidation, and inhibition of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…While immune-regulatory functions of placental extract are likely dependent on additive and synergistic effects of these components, one of potential candidates is cyclo-trans-4-L-hydroxyprolyl-L-serine, a dipeptide isolated from hydrolysates of placental extract [31, 32]. It has been reported that administration of cyclo-trans-4-L-hydroxyprolyl-L-serine ameliorates inflammation in the liver [33]. Thus, we next examined a potential effect of cyclo-trans-4-L-hydroxyprolyl-L-serine in CHS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While immune-regulatory functions of placental extract are likely dependent on additive and synergistic effects of these components, one of potential candidates is cyclo-trans-4-L-hydroxyprolyl-L-serine, a dipeptide isolated from hydrolysates of placental extract [31, 32]. It has been reported that administration of cyclo-trans-4-L-hydroxyprolyl-L-serine ameliorates inflammation in the liver [33]. Thus, we next examined a potential effect of cyclo-trans-4-L-hydroxyprolyl-L-serine in CHS.…”
Section: Resultsmentioning
confidence: 99%
“…The process of placenta acquisition and extract preparation was concordant with those for Laennec, a drug of placental extracts for liver dysfunction that has been approved by Ministry of Health, Labour and Welfare in Japan. Cyclo-trans-4-L-hydroxyprolyl-L-serine (also called as JBP485), which is isolated from hydrolysates of placental extract, was prepared as previously reported [31-33]. …”
Section: Methodsmentioning
confidence: 99%
“…HPE is enriched in enzymes, nucleic acid, vitamins, amino acids, steroids, fatty acids and minerals . HPE mediates immunotrophic, antioxidative and anti‐inflammatory responses . HPE has recently been used to treat various diseases (chronic liver diseases [CLD], menopausal syndrome, chronic fatigue syndrome, atopic dermatitis, aging and so on).…”
Section: Introductionmentioning
confidence: 99%
“…3 HPE mediates immunotrophic, antioxidative and anti-inflammatory responses. [4][5][6][7] HPE has recently been used to treat various diseases (chronic liver diseases [CLD], [8][9][10][11] menopausal syndrome, 12 chronic fatigue syndrome, 13 atopic dermatitis, aging 14 and so on). Laennec, a trade name for the hydrolysate of human placenta, has been enantioselectively synthesized by chemical means.…”
Section: Introductionmentioning
confidence: 99%
“…JBP485 (cyclo-trans-4-L-hydroxyprolyl-L-serine) is a dipeptide that was first isolated from placental extract (PE) as a mitogen for a kidney cell line, and it has subsequently been synthesized by chemical means 16 17 . Previous studies have demonstrated that JBP485 has anti-inflammatory and anti-apoptotic effects and that it exhibits protective properties for liver and gastrointestinal cells 17 18 19 20 21 . Recently, we discovered that JBP485 promotes the cell proliferation of corneal epithelium during wound healing (unpublished data).…”
mentioning
confidence: 99%